2020
DOI: 10.3390/ijms21051622
|View full text |Cite
|
Sign up to set email alerts
|

Isoform-Specific Lysine Methylation of RORα2 by SETD7 Is Required for Association of the TIP60 Coactivator Complex in Prostate Cancer Progression

Abstract: The retinoid acid-related orphan receptor α (RORα), a member of the orphan nuclear receptor superfamily, functions as an unknown ligand-dependent transcription factor. RORα was shown to regulate a broad array of physiological processes such as Purkinje cell development in the cerebellum, circadian rhythm, lipid and bone metabolism, inhibition of inflammation, and anti-apoptosis. The human RORα gene encodes at least four distinct isoforms (RORα1, -2, -3, -4), which differ only in their N-terminal domain (NTD). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…ROR-α2 K87R significantly decreased CTNND1 mRNA as compared to ROR-α2 WT and resulted in failure to increase PC-3 cell proliferation and viability. These suggests that SETD7 methylation of RORα2 promotes the recruitment of coactivator complex pontin/Tip60 to ROR-α2 target genes to support ROR-α2 oncogenic potential [75] (Figure 7). Another group published three papers in which they performed SETD7 knockdown in PCa cells [76][77][78] but only analysed the functional consequences in one of them [77].…”
Section: (B)mentioning
confidence: 96%
See 1 more Smart Citation
“…ROR-α2 K87R significantly decreased CTNND1 mRNA as compared to ROR-α2 WT and resulted in failure to increase PC-3 cell proliferation and viability. These suggests that SETD7 methylation of RORα2 promotes the recruitment of coactivator complex pontin/Tip60 to ROR-α2 target genes to support ROR-α2 oncogenic potential [75] (Figure 7). Another group published three papers in which they performed SETD7 knockdown in PCa cells [76][77][78] but only analysed the functional consequences in one of them [77].…”
Section: (B)mentioning
confidence: 96%
“…Cellular processes regulated by SETD7 in prostate cancer where it functions as a tumour promoter. SETD7 methylates ROR-alpha2 promoting its binding with TIP60 to induce CTNND1 expression and proliferation [75]. SETD7 can also promote proliferation by methylating to enhance its transcriptional activity.…”
Section: (B)mentioning
confidence: 99%
“…Among these methylases, SETD7 can regulate the growth of blood vessels in the retina 9 and inhibit the activity of chondrocytes 10 . In addition, some studies have confirmed that SETD7 is associated with the inflammatory response and apoptosis induced by cytokines 11,12 . Consequently, we hypothesized that SETD7 may be a key molecule that links inflammation, angiogenesis, and chondrocyte apoptosis.…”
Section: Introductionmentioning
confidence: 96%
“…We found that hypermethylation‐mediated downregulation of RORA was associated with poor survival in KIRC, suggesting that hypermethylated RORA might be a driver gene in that cancer. Numerous studies have reported that hypermethylation of RORA is associated with the progression of various cancers 36‐39 . However, there was also nonconformity among methylation, expression, and prognosis.…”
Section: Discussionmentioning
confidence: 99%